EDUCATION AND SUPPORT FOR MOTHERS IN PROVIDING EXCLUSIVE BREASTFEEDING AT PMB NURLELA, LUBUK PAKAM DISTRICT, DELI SERDANG REGENCY - Marliani, Marliani; Anggraini, Mia; Surbakti, Imran Saputra; Ginting , Astaria Br; Situmorang, Putri Amelia; Zai, Novi Kristiani (CV. Alina, 2025)
Background: Exclusive breastfeeding coverage in Deli Serdang Regency remains low, partly due to a lack of knowledge, limited time for working mothers, and the minimal role of health workers in providing education. Objective: To implement educational and mentoring activities for mothers with infants aged 0–12 months to increase their understanding and motivation for exclusive breastfeeding. Methods: The community service activity was conducted at the Nurlela Pre-Breastfeeding Center (PMB) in Lubuk Pakam District in May 2024. The target group was 30 mothers who were not exclusively breastfeeding. Implementation methods included counseling, interactive discussions, demonstrations of correct breastfeeding techniques, and individual counseling. Results: The activity received a positive response; there was a 53.3% increase in maternal knowledge (measured by pre- and post-tests). Some mothers who had previously been formula-feeding committed to exclusively breastfeeding their next baby. Conclusion: Education and mentoring at PMB effectively increased maternal knowledge and motivation for exclusive breastfeeding. It is recommended that these activities be conducted regularly and supported by local health workers.